Customer Relations Management of Rumah Sehat and Apotek UGM in Maintaining Customer Loyalty - Noviatun; Tunggali , Ade Putranto Prasetyo Wijiharto (Universitas Muhammadiyah Yogyakarta, 2023)
Yogyakarta is known as a city of education and tourism, in order to support national development must be based on health that pays attention to the health of its people. Therefore, the Yogyakarta city government needs to provide adequate health facilities or health services, both in terms of service and quality. As of 2022 until now, the pharmacy business is growing throughout Indonesia. This requires pharmaceutical personnel for pharmaceutical services and health supplies. Various pharmaceutical activities in pharmacies ensure that the community receives optimal drug services. The ideal concept of a pharmacy is an attitude of totality in providing services to consumers/patients. In an effort to create customer loyalty, Pharmacy Facility Owners (PSA) in collaboration with Pharmacy Manager Pharmacists (APA) need to have a good marketing strategy.. One form of marketing strategy that can help and support the business is the Customer Relationship Management (CRM) strategy. The purpose of this research is to find out how Customer Relations Management of Rumah Sehat and Apotek UGM in maintaining customer loyalty. This research is a descriptive qualitative research using data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the aspects of Customer Relationship Management are very influential in maintaining customer loyalty. This study concludes that the aspects of CRM which include email integration, lead conversion, feedback improvement, document recording, relationship management, sales calls, and email marketing have an influence on customer loyalty at Rumah Sehat and Apotek UGM. The novelty of this research is to find out the effect of CRM on customer loyalty at Rumah Sehat and Apotek UGM and how much influence CRM has on customer loyalty.